Small Airways Disease in Asthma - Gulliver, Tanya; Piedimonte, Giovanni; Eid, Nemr (Current Respiratory Medicine Reviews, 2006)
Small airway plays a major role in viral infection of the respiratory tract in infants and young children. Indeed these early viral infections have been shown to lead to airway remodeling and early development of non allergic asthma by affecting the expression of critical growth factors. In the old child and adult however, and until very recently, asthma has been considered largely a disease of the large airways. But as our understanding of asthma evolves, it now seems that the disease process in asthma is located in all parts of the tracheobronchial tree, small airways, and alveoli. Small airway remodeling has the potential to produce fixed airflow obstruction, which if untreated and unrecognized can lead chronic obstructive pulmonary disease. With the recognition of the important role of the small airways in the pathogenesis of asthma in infants as well as in adults, more aggressive modalities of treatment are urgently needed in order to have a positive impact on asthma outcome. This article will review the impact of early viral infections on airway remodeling in infants, the role that small airways play in older asthmatics, and finally the potential role of new HFA formulation for the treatment of asthma.
Keywords: inflammation